IDENTIFIKASI FAKTOR PENDUKUNG DAN FAKTOR PENGHAMBAT PENGUASAAN SKILL PEMERIKSAAN FISIK PADA MAHASISWA PROGRAM D-3 KEPERAWATAN UNIVERSITAS MUHAMMADIYAH MALANG - Indah Dwi Pratiwi (Universitas Muhammadiyah Malang, 2009)
Physical assessment skill is depend on many factors, clinical experiences and composure on doing assessment technique is very important. Negative or positive false will reduce those meticulous techniques. However, assessment result could be different according to techniques that used by different assessor, various equipment or when it done for different patients. From proposal study on 96 of first grade nursing student scores mean in UMM about physical assessment skill which are attained from campus laboratory practices, result are 12% were very good, 31% were good, 46% were fair and 11% were poor. The objectives of this research is to know the supporting and opposing factors on physical assessment skill in nursing diploma student in Muhammadiyah University of Malang. Research design were using observational descriptive study. It held on first period of internal research on July to November 2007. The population of this research were nursing diploma student in Muhammadiyah University of Malang and the second grade of nursing student were the samples. Sampling technique were using purposive sampling. Data analyzes used Guttman Scale Standart. Fom the research, the percentage of supporting internal factor were 59% and opposing factor were 41,0 % on physical assessment skill in nursing diploma student in Muhammadiyah University of Malang. The percentage of supporting external factor were 57.9% and opposing factor were 42.1 % on physical assessment skill in nursing diploma student in Muhammadiyah University of Malang. Conclusion: Supporting factor for increasing physical assessment skill on internal factor are (59%) and on external factor are (57,9%). Opposing factor in order to increase physical assessment skill on internal factor are (41%) and on external factor are (43.1%). Internal factor on resource comprehension and literature using from lecturer is quite less on percentage of 50.6%. On the other hand, from external factors about guidance book is relatively less on percentage of 45.6%. Keywords: Supporting factor, Opposing factor, Physical assessment skill